Manajemen Perioperative pada Pasien Tumor Craniopharygioma - Andika Metrisiawan; Nova Juwita; I Putu Pramana Suarjaya (Majalah Anestesia & Critical Care, 2023)
Craniopharyngiomas are benign histological brain tumors originating less frequently fromembryonic pituitary gland tissue that are seen most frequently in children between the ages of 5and 10 years. In this case report we present a 25-year-old patient with a craniopharyngiomatumor. Patients with decreased consciousness since 4 months before admission to the hospital,which started with memory loss that was getting worse and more difficult to communicate. Thepatient was diagnosed with a brain tumor and underwent surgery for tumor therapy in 2018. Theprocedure was performed using a transcranial approach. Considerations for preoperativeanesthesia should include evaluation of radiological features to identify tumor mass andpreoperative neurologic status. Other examinations of concern include examination of blood gasanalysis and examination of electrolytes. The goals of treatment can be to remove the tumor,reduce or control the size of the tumor.